Factors associated with postpartum fatigue: an exploration of the moderating role of resilience - Baattaiah, Baian A.; Alharbi, Mutasim D.; Aldhahi, Monira I.; Khan, Fayaz (Frontiers in Public Health, 2024)
Background: Postpartum fatigue (PPF) can impair the physical and mental well-being of women. The aims of this study were to assess the associations between fatigue and maternal health-related variables, specifically, sleep quality, depression symptoms, and resilience, and to explore the moderating role of resilience in the relationships between sleep quality, depression symptoms, and fatigue. Methods: This cross-sectional study used data collected from mothers during the postpartum period via an online platform. PPF was assessed using the Fatigue Severity Scale, whereas sleep quality and depression symptoms were assessed using the Pittsburgh Sleep Quality Index and Edinburgh Postnatal Depression Scale, respectively. The Brief Resilience Scale was used to assess resilience. Simple and multiple binary logistic regression analyses were performed to examine the association of each independent variable with PPF and to determine the most significant predictors of PFF. The data were analyzed using SPSS, and structural equation modelling was performed using AMOS 23. A moderation analysis was performed to explore the moderating role of resilience using the Hayes PROCESS macro. Results: A total of 1443 postpartum mothers were included in the analysis. The simple binary logistic regression analysis showed that having chronic disease (odds:1.52; p=0.02), mother’s age (odds:0.97; p=0.03), mother’s body mass index (odds:1.03; p=0.01), depression symptoms (odds:1.09; p≤0.001), sleep quality (odds:1.17; p≤0.001), and resilience (odds:0.42; p≤0.001) all contributed to fatigue during postpartum. Multivariate logistic regression showed that the mother’s BMI, sleep quality, depression symptoms, and resilience were significant predictors of PPF. Moderation analyses showed that resilience was not a significant moderator between the main effects of sleep quality and fatigue (interaction effect: β=0.01, p=0.31, 95% CI:−0.01 to 0.04) or between the main effects of depression symptoms and fatigue during postpartum (interaction effect: β=0.01, p=0.82, 95% CI:−0.01 to 0.02). Conclusions: Given the deleterious effects of PPF on maternal health outcomes, factors associated with PPF should be assessed regularly. In addition to mothers’ BMI, sleep quality, and depression symptoms, resilience could also be a crucial factor in predicting fatigue severity during this critical time for mothers even though it was not a significant moderator among this sample.